(3JWhQ GdGbJUGO GdeYQaj hGfYcGSGJg Ydi GbJUGOGJ GdOhd s - (3aQjO eMehO(B, (3SGdj eMeOs ((3YeGfs (3OGQ GdGHJcGQ ddfTQ hGdJhRjYs, 2023)
(3GdEWGQ GdfXQj ddGbJUGO GdeYQaj, NdajI Yf GdGbJUGO GdeYQaj, eaghe GdGbJUGO GdeYQaj, CSGSjGJ hQcGFR GdGbJUGO GdeYQaj, NWhGJ HfGA GbJUGO jbhe Ydi GdeYQaI, fXQjI Gdfeh GdLOjOI, JWhQ fXQjI Gdfeh GdLOjOI, GdLGfH GdJcfhdhLj aj fXQjI Gdfeh GdLOjOI, NUGFU GdeYQaI habG dfXQjI Gdfeh GdLOjOI, GdEbJUGO GdeYQaj aj GaQjbjG, eDTQGJ Yf GdGbJUGO GdeYQaj aj GaQjbjG, JcfhdhLjG GdGJUGdGJ hGdeYdheGJ aj bWGY GdGYeGd GdEaQjbj, GdGSJKeGQGJ GdGaQjbjI aj bWGY GdGJUGdGJ, eTQhYGJ JcfhdhLjG GdGJUGdGJ hGdeYdheGJ aj GaQjbjG, TQcGJf GdGJUGdGJ aj GaQjbjG, YQV feGPL dhVY GdGbJUGO GdeYQaj aj GdbGQI GdGaQjbjI, hVY GdGbJUGO GdeYQaj aj eUQ, hVY GdGbJUGO GdeYQaj aj JGdeZQH, hVY GdGbJUGO GdeYQaj aj ehQjTjhS, hVY GdGbJUGO GdeYQaj aj LfhH GaQjbjG, bjGS hVY GdGbJUGO GdeYQaj aj GaQjbjG, bjGS GdGSJYOGO GdGdcJQhfjddOhd GdGaQjbjI, bjGS GdYdGbI Hjf Gdfeh GdGbJUGOj hJWhQ bWGY GdGJUGdGJ aj GaQjbjG, CKQ GdGbJUGO GdeYQaj Ydi GdGbJUGOGJ GdGaQjbjI, aQU hJMOjGJ GfOeGL GaQjbjG ddGbJUGO GdeYQaj, ChdhjI GdJfejI GdeYQajI aj GaQjbjG, SHd ehGLgI GdOhd GdGaQjbjI ddJMOjGJ GdeYQajI(B.s
Keywords: (3GdEbJUGO GdOhdjs; (3GdGbJUGO GdeYQajs; (3GdJNWjW GdEbJUGOjs; (3GdJfejI GdEbJUGOjIs